THU0621 VERY LOW PREVALENCE OF ULTRASOUND DETERMINED TENDON ABNORMALITIES IN HEALTHY SUBJECTS THROUGHOUT THE AGE RANGE: OMERACT ULTRASOUND MINIMAL DISEASE STUDY. (June 2019) - Trickey, Jeanette; Sahbudin, Ilfita; Bortoluzzi, Alessandra; Iagnocco, Annamaria; Pineda, Carlos; Sifuentes-Cantú, Cesar; Ciurtin, Coziana; Sokolova, Cristina Reategui; Fodor, Daniela; Hauge, Ellen-Margrethe; Naredo, Esperanza; Vreju, Florentin Ananu; et al.
Abstract : Background: Tenosynovitis (TS) is a common, often clinically undetectable finding in Rheumatoid Arthritis (RA). Recent data showed TS on ultrasound (US) has a role in predicting outcome in early disease and flare in clinical remission. However data is limited on US measured TS in healthy subjects (HS), none specifically encompassing the older age range when RA commonly presents. Objectives: This OMERACT study aimed to determine prevalence of US measured tendon abnormalities in HS throughout the age range. Methods: Adult HS without: joint pain (VAS <10/100), hand osteoarthritis (ACR criteria), or inflammatory arthritis were recruited in 23 international centres from Aug 2017-Dec 2018. MCP, PIP and wrist joints were clinically examined. Bilateral digit flexor (DF) 1-5 and extensor carpi ulnaris (ECU) tendons were scanned for tenosynovial hypertrophy (TSH) and power Doppler (PD) signal and graded (OMERACT US scoring system 1 ). A comparison cohort of DMARD-naive patients with RA (ACR-EULAR 2010 and/or 1987 criteria) at presentation was taken from the Birmingham Early Arthritis (BEACON) inception cohort, who underwent identical tendon US assessment. They were grouped into ≤12 and > 12 weeks from symptom onset. Results: Data from 899 HS and 144 RA patients were included. Prevalence of TSH and particularly PD abnormalities in HS was very low at all ages, and was all grade 1 except in one individual ECU tendon. ECU TSH grade≥1 was more common than DF grade≥1 in the older HS groups, and less common in the 18-39 age group (p=0.011). TSH and PD of grade ≥1 were common in RA patients, with DF PD abnormalities more common in early disease (p=0.02). Conclusion: Low prevalence of TSH or PD abnormalities in tendons of HS even in old age suggests US determined TS will be a robust tool in clinically managing RA. References: [1] Naredo E, D'Agostino MA, et al. Reliability consensus-based US score TS RA. ARD.2013;72(8):1328-34 Disclosure of Interests: Jeanette Trickey: None declared, Ilfita Sahbudin: None declared, Alessandra Bortoluzzi: None declared, Annamaria Iagnocco: None declared, Carlos Pineda: None declared, Cesar Sifuentes-Cantú: None declared, Coziana Ciurtin: None declared, Cristina Reategui Sokolova: None declared, Daniela Fodor: None declared, Ellen-Margrethe Hauge: None declared, Esperanza Naredo Consultant for: Abbvie, Speakers bureau: AbbVie, Roche, Bristol-Myers Squibb, Pfizer, UCB, Lilly, Novartis, Janssen, and Celgene GmbH, Florentin Ananu Vreju Consultant for: abbvie and novartis, Speakers bureau: abbvie, novartis, pfizer, sandoz, eli lilly, ucb pharma, Garifallia Sakellariou: None declared, George Bruyn : None declared, Georgios Filippou Speakers bureau: Laborest, Abbvie, BMS, Sanofi, Giuliana M.C. La Paglia : None declared, Gustavo Leon: None declared, Helen Keen: None declared, Hilde Berner Hammer Grant/research support from: AbbVie, Pfizer and Roche, Paid instructor for: AbbVie, Pfizer, UCB, Novartis, Roche, Speakers bureau: AbbVie, Pfizer, UCB, Novartis, Roche, Ilaria Tinazzi: None declared, Irene Azzolin: None declared, Jacek Fliciński: None declared, James Wilton: None declared, Kei Ikeda: None declared, Lene Terslev Speakers bureau: Speakers fee from : Roche, Novartis, Pfizer, MSD, BMS, Celgene, Mads Ammitzbøll-Danielsen: None declared, Mads Nyhuus Bendix Rasch: None declared, Marcin Milchert: None declared, Maria Stoenoiu Grant/research support from: Abbvie, Roche, Wyeth, Marion Kortekaas: None declared, Marwin Gutierrez: None declared, Mihaela Maruseac: None declared, Mohammed A Mortada: None declared, Philippe Carron: None declared, Rositsa Karalilova: None declared, Ruth Wittoek: None declared, Sarah Ohrndorf: None declared, Takeshi Suzuki: None declared, Teodora Serban: None declared, Maria-Antonietta d'Agostino: None declared, Andrew Filer: None declared